PENGARUH PERILAKU KEPEMIMPINAN CAMAT TERHADAP MOTIVASI KERJA PEGAWAI DI KANTOR CAMAT NGABANG KABUPATEN LANDAK - Hendra Saputra E.42009053 (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2022)
This Writing Skripsi is intended to lay open the behavioral influence leadership of Sub-Regency chief to motivation work officer in Office Ngabang  Sub-Regency Chief of Landak Regency and also to fulfill one of condition reach for the college degree of strata 1 (one) area of  Public Administration Science in Faculty of Social Science and Politics of University of Tanjungpura Provinsi West Borneo. This research is inclusive of quantitative research type with the hypothesis examination. Population in this research amount to 31 people by sampel 30 people, while 1 people is Sub-Regency chief to be assessed by the its leadership behavior. Technique of data collecting use the enquette which have in test-drive beforehand and tested the validity and also its reliabilitas. Technique analyse used is correlation of linear product moment and regresi modestly. From research result, behavioral of leadership used by Sub-Regency chief of Ngabang is monitoring behavior. Result of research show the correlation of equal to 0,588 which its meaning is signifikansi at coefficient international 0,40 - 0,599 and r calculate the > r tables of ( 0,588 > 0,463) with the mistake level 1%, that way hence hypothesis raised to be accepted. Result of analysis regresi obtain;get the equation Y = 16,844 + 0,530X which its meaning motivate the job influenced by leadership behavior. Result of test of determinant coefficient obtain;get the value r2 of equal to 0,3457 indicating that behavioral variable of leadership have an effect on to motivation work equal to 34,57%. Matter of this means good leadership behavior have the influence in improving motivation work the. The rest 65,43% influenced by other;dissimilar variable which is not checked, for example environment work, discipline, observation and others. Keyword : Behavioral of Leadership, Motivate Job